Vocational Cadets Self-Concept about the Majors They Occupy and Their Implications in Counseling Services - Yuni Agustina; Yulidar Ibrahim (Jurnal Neo Konseling, 2019)
Self-concept one's view of himself which involves what he knows and feels about his behavior, the contents of his mind, and how his behavior affects other people. Individuals who develop their self concepts well will grow in self-confidence, brave, passionate in carrying out activities including learning, have self-confidence, dare to get along, often present themselves, become an independent person and have a positive view of him. The purpose of this study is to describe the self-concept of cadets about the majors they occupy viewed from aspects of knowledge, expectations and assessments. The type of research used is descriptive research. The population of the research is 590 cadets of SMK. Samples were taken using stratifed random sampling technique, so as to get a total sample of 238 cadets/i. The study was conducted by administering the questionnaire instrument. Data were analyzed by percentage analysis. The research findings show the results of (1) the self concept of cadets about the majors they occupy as a whole is in quite good category, (2) the cadets' self concept of the majors they occupy is seen from the knowledge is in the quite good category (3) concepts cadets themselves about the majors they occupy seen from expectations in the category of less good 4) cadets self-concept about the majors they occupy seen from the assessment in the category is quite good.